O ensino de literatura na escola regular como brecha para o letramento crítico - Caroline Martins dos Santos (2016)
English language teaching in public schools has been much discussed based on official documents which suggest the critical education approach and the formation of citizens, as discussed in the Orientações Curriculares para o Ensino Médio (OCEM) (BRASIL, 2006).Some papers discuss the importance of literature for foreign language teaching, besides other factors which contribute to the critical education of the individual (FESTINO, 2011; LOURENÇO, 2011; WIELEVICKI, 2013; XAVIER, 2014). However, the Brazilian public school only offers space for literature in the Portuguese language teaching, and the teaching of foreign languages is concerned only with the linguistic aspect of the language (BRASIL, 2006). This paper intended to investigate the space that literature can have in the foreign language classroom in public schools, from three activities applied to thirty students from a municipal school in Belo Horizonte. The activities were analyzed from the perspectives of students and participant teacher through classroom observation, interviews, questionnaires and analysis of the responses of the students in the activities. Thus, it was observed that, in addition to the opportunity to teach the linguistic aspect in the literary text, opportunities to promote critical literacy are also present (CERVETTI; PARDALES; DAMICO, 2001; McLAUGHLIN; DeVOOGD, 2004), as the English-language literature texts may function as cracks (DUBOC, 2012) which allow for the use of a critical literacy approach.